Effects of benzo[a]pyrene on the reproductive axis: Impairment of kisspeptin signaling in human gonadotropin-releasing hormone primary neurons. (15th January 2023) - Guarnieri, Giulia; Becatti, Matteo; Squecco, Roberta; Comeglio, Paolo; Garella, Rachele; Tamburrino, Lara; Marchiani, Sara; Vignozzi, Linda; Vannelli, Gabriella Barbara; Maggi, Mario; Morelli, Annamaria
Abstract: The neuroendocrine control of reproduction is strictly coordinated at the central level by the pulsatile release of gonadotropin-releasing hormone (GnRH) by the hypothalamic GnRH neurons. Alterations of the GnRH-network, especially during development, lead to long-term reproductive and systemic consequences, also causing infertility. Recent evidence shows that benzo[a]pyrene (BaP), a diffuse pollutant that can play a role as an endocrine disruptor, affects gonadal function and gamete maturation, whereas data demonstrating its impact at hypothalamic level are very scarce. This study investigated the effects of BaP (10 μM) in a primary cell culture isolated from the human fetal hypothalamus (hfHypo) and exhibiting a clear GnRH neuron phenotype. BaP significantly decreased gene and protein expression of both GnRH and kisspeptin receptor (KISS1R), the master regulator of GnRH neuron function. Moreover, BaP exposure increased phospho-ERK1/2 signaling, a well-known mechanism associated with KISS1R activation. Interestingly, BaP altered the electrophysiological membrane properties leading to a significant depolarizing effect and it also significantly increased GnRH release, with both effects being not affected by kisspeptin addition. In conclusion, our findings demonstrate that BaP may alter GnRH neuron phenotype and function, mainly interfering with KISS1R signaling and GnRH secretion and therefore with crucial mechanisms implicated in the central neuroendocrine control of reproduction. Graphical abstract: Image 1 Highlights: The widespread pollutant BaP can act as an endocrine disruptor affecting fertility. Human hypothalamic GnRH neurons are responsive to BaP insult. BaP affects human GnRH neuron phenotype and function. BaP interferes with KISS1R signaling and GnRH secretion. BaP impairs human GnRH neuron responsiveness to kisspeptin.